The Study of Parameter Sensitivity of SWAT Model for Runoff and Groundwater: A Case Study of Phetchaburi Basin - แมงสาโมง วนัชพร; คอแด๊ะ ฮาซัน (Princess of Naradhiwas University Journal, 2018)
Soil and Water Assessment Tool (SWAT) is important for planning and sustainable use of water resources to meet various demands. Since it is a distributed parameter values model, the user must set parameters to suit the studied area. The purpose of this research was to investigate the sensitivity of SWAT model parameters on the runoff and groundwater content. This case study of Phetchaburi Basin used the relative sensitivity index to determine the sensitivity of parameters. The results of this research showed that the top 4 ranking of parameters sensitivity value index to runoff were: 1) the curve number (Cn2), 2) the available water capacity (Sol_Awc), 3) the soil evaporation compensation factor (Esco), and 4) the saturated hydraulic conductivity (Soil_K). While the top 5 ranking of parameters sensitivity value index to groundwater were: 1) the available water capacity of soil (Sol_Awc), 2) the groundwater delay (Gw_Delay), 3) the soil evaporation compensation factor (Esco), 4) the saturated hydraulic conductivity (Soil_K), and 5) the curve number (Cn2). The results of this study could be further used for SWAT mode calibration to simulate runoff in Phetchaburi Basin in the future.